An Acceptable Meaning of the Constitution - Gary C. Leedes (Washington University Law Quarterly, 1984)
Judges clarify the Constitution in many plausible but different ways. The natural inclinations of a judge influence his starting premises. Some judges by nature prefer judicial restraint; others prefer selective judicial activism. The art of interpreting the Constitution involves the act of thinking, which, if disciplined, is not necessarily the same as illegitimate, judicial subjectivity. This is the hermeneutic insight presented in this Article.
Keywords: Jurisprudence; Constitutional interpretation; Hermeneutics; Law; United States